Case report: Aseptic splenic abscesses in childhood-onset systemic lupus erythematosus - Sritharan, Shobashenee; Lau, Peter Sie-Teck; Manan, Kamilah; Mohan, Anand (Frontiers in Pediatrics, 2023)
Background Systemic lupus erythematosus (SLE) can involve any organ system and cause a wide range of manifestations. Noninfectious inflammatory lesions termed aseptic abscesses have been reported in some autoimmune and autoinflammatory conditions but not in childhood-onset SLE. In this report, we highlight the unusual finding of occult splenic abscesses in two children diagnosed with SLE who had no evidence of concomitant infection. Case presentation An 8-year-old and an 11-year-old were admitted separately to the hospital with fever for 7 and 14 days, respectively. In the younger child, a generalized rash preceded the fever. Both had been well, with no significant past medical history prior to the onset of the illness. In both girls, abdominal ultrasonography showed multiple small hypoechoic lesions suggestive of abscesses scattered throughout the spleen. Their C-reactive protein and blood cultures were negative, and symptoms persisted despite intravenous antibiotics. Fulfilling the clinical and immunologic criteria for diagnosis, both were ultimately diagnosed with childhood-onset SLE. Rapid recovery of symptoms and complete resolution of the abscesses ensued with corticosteroids and immunosuppressive therapy. Conclusions These two cases suggest that aseptic splenic abscesses may occur in childhood-onset SLE. Autoimmune conditions such as SLE should be included in the differential diagnosis of children with occult splenic abscesses.